Policy analysis of selected transport sector options for mitigating air pollution : the case of Kathmandu valley - Pradhan, Dinesh Lal; Shrestha, Ram M.; Bhattacharya, Sribas C.; Dang, G. V.; Tabucanon, Mario T.; King's Scholarship (Government of Thailand) (Bangkok : Asian Institute of Technology, 1994)
Air quality in the valley is degrading gradually due to old vehicles, incomplete combustion of fossil fuels, lower fuel quality, increasing vehicle strength, congested road and industrial emissions. Transport sector is the major contributor to the acute air quality problems in the valley. A concerted strategy is needed to meet the challenges, one that gives priority to options that produce maximum benefit at minimum cost. This study examined various strategies for reducing air pollution and achieving energy savings. The results of the study indicate that a number of measures could be taken to reduce the environmental impacts of transport. Emission factors corresponding to vehicles are linked to the fuel consumption values to estimate total emissions of major pollutants CO, HC, NOx, S02, Pb and TSP. Total energy demand and vehicle emissions are estimated for 1993/94 and projections of the same for the future year 2003/4 are made. Seven scenarios are considered to study the effects of alternative policy initiatives on transport sector energy consumption and emissions. The options considered are increasing the share of mass transport, improving road conditions, introducing inspection and maintenance program, improving fuel quality, use of control devices, increasing fuel prices and reformulating vehicle tax system. These options have been considered against the business as usual scenario (BAU) for their impact on emissions and energy consumption by transport sector in Kathmandu Valley. All the options considered have shown net fuel savings (except the option of using control devices) and reduction of emissions as compared with the BAU case. It is found that increasing the share of mass transport by 10% in total passenger kilometer would reduce the total transport sector pollution by 15.7% in year 2003/4. Due to the increase in share of buses in total passenger kilometer, additional diesel requirement was estimated to be 6,000 Kl while there would an estimated saving in gasoline consumption of 14,482 Kl in year 2003/4 and foreign exchange conserved in the same year is estimated about 1. 84 million dollars. Road improvements show an impressive potential for fuel savings and emission reductions. The foreign exchange conserved by this way is estimated to be about 13 .15 million dollars and reductions are about 33% in the year 2003/4. This underscores the importance of providing the requisite infrastructure for the vehicles to operate at their best. The option of using control devices shows that using catalytic converters in cars, and trap oxidizer and EGR on diesel driven vehicles may not have significant impact on total emission reduction but the user costs for this option are very high. Finally ranking of selected options has been done under various criteria e.g. economic and financial, social, administrative, political and institutional by using Analytical Hierarchy Process model. Increasing the share of mass transport and improving road conditions have been ranked first and second most preferred options respectively on all conditions. It is concluded that no single measure could on its one achieve the gigantic target of containing the growth of fuel consumption and emissions. It is observed that a successful policy would have to include a mixture of the various measures.
A thesis submitted in the partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Air quality management -- Nepal -- Kathmandu Valley; Energy consumption -- Nepal -- Kathmandu Valley